PENGARUH PERSEPSI KEMUDAHAN, GAYA HIDUP, DAN KEPERCAYAAN TERHADAP MINAT PENGGUNAAN QRIS PADA MAHASISWA AKUNTANSI UPN “VETERAN” JAWA TIMUR - Widya; Trisnaningsih, Sri; Vendy, Vicky (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Technological developments have created new innovations in non-cash payment methods, namely QRIS. QRIS issued by Indonesian banks allows various electronic payment applications to use the same QR code to facilitate payment transactions, so that QRIS users continue to increase every year. However, the increase in the number of users cannot be separated from the driving factors that make users interested in making transactions using QRIS. The aim of this research is to determine the influence of perceived convenience, lifestyle and trust on interest in using QRIS among accounting students. Data was obtained from 91 respondents who were accounting students from the 2020-2022 class at UPN